Children as partners with adults in their medical care. Issue 4 (6th January 2006) - Alderson, P; Sutcliffe, K; Curtis, K
Abstract : Aims: To investigate the seldom published views of children with type 1 diabetes about their condition and ways in which they share in managing their medical and health care with adults. Methods: Semi-structured, tape recorded interviews, during 2003, with a purposive sample of 24 children aged 3–12 years who have type I diabetes and who attend two inner London hospitals and one hospital in a commuter town. Results: The children reported high levels of understanding, knowledge, and skill gained from their experience of living with diabetes and constantly having to take account of the condition and their paediatrician's guidance. Their key goals were to be "normal" and "just get on with their lives". Discussion: The interviews showed that children's experiences of diabetes tended to enable them to make informed, "wise" decisions in their own best interests, even at a young age. They achieved a complicated balance between the sometimes competing goals of social health "being normal" and physiological health in controlling glycaemia. Their competence supports approaches in children's rights and in policy makers' aims that people with diabetes—including children—gain more knowledge, skills, and responsibility for their own care in partnership with healthcare professionals. Consent is usually considered in relation to surgery; however the children showed how they constantly dealt with decisions about consent or refusal, compliance with, or resistance to their prescribed treatment. Their health depends on their informed commitment to medical guidance; more research is needed about the daily realities of children's committed and responsible co-management of their chronic illness.